Savouring morality: moral satisfaction renders food of ethical origin subjectively tastier - Bratanova, B. (2015)
Past research has shown that the experience of taste can be in?uenced by a range of external cues, especially when they concern food’s quality. The present research examined whether food’s ethicality – a cue typically unrelated to quality – can also in?uence taste. We hypothesised that moral satisfaction with the consumption of ethical food would positively in?uence taste expectations, which in turn will enhance the actual taste experience. This enhanced taste experience was further hypothesised to act as a possible reward mechanism reinforcing the purchase of ethical food. The resulting ethical food ?moral satisfaction ?enhanced taste expectations and experience ?stronger intentions to buy/willingness to pay model was validated across four studies: one large scale international survey (Study 1) and three experimental studies involving actual food consumption of different type of ethical origin – organic (Study 2), fair trade (Study 3a) and locally produced (Study 3b). Furthermore, endorsement of values relevant to the food’s ethical origin moderated the effect of food’s origin on moral satisfaction, suggesting that the model is primarily supported for people who endorse these values.